Respuesta :
If you would like to solve the system of equations by substitution, you can do this using the following steps:
3/8x + 1/3y = 17/25
x + 7y = 8 ... x = 8 - 7y
______________
3/8x + 1/3y = 17/25
3/8 * (8 - 7y) + 1/3y = 17/25
3 - 21/8 * y + 1/3 * y = 17/25
- 21/8 * y + 1/3 * y = 17/25 - 3
-63/24 * y + 8/24 * y = 17/25 - 3
-55/24 * y = 17/25 - 75/25
-55/24 * y = -58/25
55/24 * y = 58/25
y = 58/25 * 24/55
y = 1392/1375
x = 8 - 7y = 8 - 7 * 1392/1375 = 8 - 9744/1375 = 1256/1375
(x, y) = (1256/1375, 1392/1375)
The correct result would be (1256/1375, 1392/1375).
3/8x + 1/3y = 17/25
x + 7y = 8 ... x = 8 - 7y
______________
3/8x + 1/3y = 17/25
3/8 * (8 - 7y) + 1/3y = 17/25
3 - 21/8 * y + 1/3 * y = 17/25
- 21/8 * y + 1/3 * y = 17/25 - 3
-63/24 * y + 8/24 * y = 17/25 - 3
-55/24 * y = 17/25 - 75/25
-55/24 * y = -58/25
55/24 * y = 58/25
y = 58/25 * 24/55
y = 1392/1375
x = 8 - 7y = 8 - 7 * 1392/1375 = 8 - 9744/1375 = 1256/1375
(x, y) = (1256/1375, 1392/1375)
The correct result would be (1256/1375, 1392/1375).